Contents of black carbon in some surface dusts from Zhejiang Province - HUANG Jia-ming; WANG Xiao-xu; WANG Yang; ZHANG Ming-kui (浙江大学学报. 农业与生命科学版)
To understand the effects of human activity on accumulation of black carbon in surface dusts, 174 of surface dust samples were collected from Zhejiang Province. The surface dust samples were taken from different areas which included indoor in countryside, outdoor in countryside, manufacture with coal as fuels, coach station, indoor in urban residential area, outdoor in urban residential area, and office room. The contents of black carbon in the surface dust samples were characterized by chemical method. The results showed that the contents of black carbon in the dusts varied greatly with variation coefficient of 61.04%, and ranged from 1.47 to 25.47 g·kg-1, and averaged 9.24 g·kg-1. Most of the samples (45.98%) had black carbon contents ranging from 5 to 10 g·kg-1. Mean contents of black carbon in the surface dusts from different areas decreased in the sequence of indoor in countryside > manufacture with coal as fuels > coach station > outdoor in countryside > outdoor in urban residential area > indoor in urban residential area > office room. The proportion of black carbon in total organic carbon ranged from 14.35% to 63.47% with mean of 40.55%, and decreased in the sequence of coach station > manufacture with coal as fuels > outdoor in urban residential area > indoor in urban residential area > office room > indoor in countryside > outdoor in countryside. Correlation analysis showed that contents of black carbon in the dusts were positively and significantly correlated with its total organic carbon. Black carbon content of surface dusts was generally higher than that of soils, and lower than that of aerosol. The proportions of black carbon in the dust total organic carbon were also higher than those of soils. The results above suggest that the surface dusts can be a source of black carbon in environments in earth.